Peningkatan Agilitas Kompetensi ASN melalui Psychological Safety dan Growth Mindset Pada Dinas Ketahanan Pangan Provinsi Sulawesi Barat - Distapang, Ratna; Ramli S, Ramli S; Aqil, Muhammad; Nurfaidah, Nurfaidah (Pascasarjana Universitas Muhammadiyah Mamuju, 2026)
The research employed a quantitative approach with a descriptive survey design. The research object consisted of civil servants within the institution, with a total population and sample of 47 respondents using a total sampling technique. Primary data were collected through an online structured questionnaire using a five-point Likert scale. Data analysis was conducted using SPSS version 25, including validity and reliability tests, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results indicate that psychological safety does not have a significant effect on competency agility with a significance value of 0.226 (>0.05) and t value of 1.228 (<1.681). In contrast, growth mindset shows a significant effect with a significance value of 0.011 (<0.05) and t value of 2.664 (>1.681). Simultaneously, both variables significantly influence competency agility with an F value of 20.919 (>3.21) and a significance level of 0.000. The coefficient of determination (R²) of 0.487 reveals that 48.7% of the variance in competency agility is explained by the two independent variables